Lateral pretrichial subcutaneous brow lift with upper eyelid blepharoplasty - Aynur Aliyeva; Elif Sari (Scientific Reports)
Abstract This study evaluates the combined approach of lateral temporal subcutaneous brow lift (LTSBL) and upper blepharoplasty to improve both brow and eyelid aesthetics. An analysis was conducted on 28 female patients (mean age: 47 ± 6.3 years) who underwent the combined procedure between January 2023 and September 2024. Preoperative and postoperative photographs were analyzed using Westmore’s ideal eyebrow measurements. Satisfaction was assessed with a visual analog scale (VAS) questionnaire. The combined surgery demonstrated significant improvement in brow positioning. Follow-up was conducted at an average of 11 ± 2 months (range: 3–13 months) to assess the mid-term stability of brow position. The A-C line (lateral brow) showed a 50% improvement, increasing from 46 mm (SD ± 4.6) to 71 mm (SD ± 5.1) (p = 0.02). The D-E line (brow apex) improved by 45%, from 35 mm (SD ± 5.6) to 50.75 mm (SD ± 4.5) (p = 0.04). Horizontal alignment (B-C) improved by 25%, contributing to overall brow symmetry. Patient satisfaction was high, with 89% expressing satisfaction and 11% reporting high satisfaction. Combining LTSBL with upper blepharoplasty provides comprehensive periorbital rejuvenation, addressing lateral brow ptosis and upper eyelid excess. This technique offers high aesthetic satisfaction with minimal complications, making it an effective option for patients seeking enhanced upper facial harmony.